Implementasi Proyek Penguatan Profil Pelajar Pancasila dengan Tema Suara Demokrasi di SMP Negeri 1 Bontomarannu - Aprilia Dewi Umalia; Mustari Mustari; Mustaring Mustaring; Najamuddin Najamuddin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) at SMP Negeri 1 Bontomarannu, analyze the supporting factors and inhibiting factors of P5 implementation at SMP Negeri 1 Bontomarannu. Using descriptive qualitative methods, by conducting observations, interviews and documentation. The results showed that the implementation of P5 with the theme Voice of Democracy in the election of the student council chairman provided a contextual and meaningful learning experience for students. This activity not only introduces the democratic process in the school environment, but also becomes a means of strengthening character and developing student competence. The dimension of Belief and Fear of God Almighty is evident from the integration of religious values in the election process which emphasizes honesty, responsibility, and prayer in every stage of the activity. The Critical Reasoning dimension is achieved through vision-mission analysis activities, debates, and rational decision-making. The Global Diversity dimension is seen in the interaction of students who reflect tolerance, empathy, and the ability to appreciate differences. However, the obstacles in the implementation of P5 are the readiness of facilitators, the preparation of modules, and the monotony of project implementation activities